2012
DOI: 10.1371/journal.pone.0039453
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Habitat Disturbance and Ecological Divergence between Incipient Species of the Malaria Mosquito Anopheles gambiae

Abstract: BackgroundAnthropogenic habitat disturbance is a prime cause in the current trend of the Earth’s reduction in biodiversity. Here we show that the human footprint on the Central African rainforest, which is resulting in deforestation and growth of densely populated urban agglomerates, is associated to ecological divergence and cryptic speciation leading to adaptive radiation within the major malaria mosquito Anopheles gambiae.Methodology/Principal FindingsIn southern Cameroon, the frequency of two molecular for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
196
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(225 citation statements)
references
References 51 publications
26
196
2
1
Order By: Relevance
“…Finally, due to the extreme association between the most effective vectors of the An. gambiae complex and human habitats, a long-standing hypothesis has suggested that human-driven selection is the main modulator of ecological divergence between and within species (Coluzzi et al 1979(Coluzzi et al , 2002Kamdem et al 2012;Caputo et al 2014). Consistent with this hypothesis, we have found that urban and suburban mosquitoes are genetically differentiated from rural populations and exhibit strong signatures of recent selection at loci containing xenobiotic resistance genes.…”
Section: Genomic Signatures Of Selectionsupporting
confidence: 87%
See 2 more Smart Citations
“…Finally, due to the extreme association between the most effective vectors of the An. gambiae complex and human habitats, a long-standing hypothesis has suggested that human-driven selection is the main modulator of ecological divergence between and within species (Coluzzi et al 1979(Coluzzi et al , 2002Kamdem et al 2012;Caputo et al 2014). Consistent with this hypothesis, we have found that urban and suburban mosquitoes are genetically differentiated from rural populations and exhibit strong signatures of recent selection at loci containing xenobiotic resistance genes.…”
Section: Genomic Signatures Of Selectionsupporting
confidence: 87%
“…3D-F). All populations described as "urban" were collected from the most urbanized areas of the city, which are characterized by a high frequency of built environments as described in Kamdem et al (2012).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…gambiae s.s . prefers wetter areas, with small and ephemeral water bodies (Lehmann, Diabate, & Diabaté, 2008); species preferences seem different in forests of Central Africa (Kamdem et al., 2012). Dabiré et al.…”
Section: Discussionmentioning
confidence: 99%
“…coluzzii and An. gambiae, show a partial but marked ecological differentiation as described above, with M predominant in more urbanised, more polluted environments with longer-lasting, more predator-infested breeding habitats; whereas S predominates in more rural settings (Kamdem et al, 2012).…”
Section: The Transmission Of Malariamentioning
confidence: 75%